Peran Job Demands dan Work-Life Balance Terhadap Work Engagement pada Karyawan Operasional Kontraktor Pertambangan Batubara - Khairun Nisa (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
This article aims to synthesize empirical evidence regarding the relationship between Job demands and work-life balance on work engagement among operational employees in coal mining contractor industries through a systematic literature review (SLR). The issue focuses on high work demands, roster systems, production targets, and occupational safety risks that potentially affect employee engagement in mining operations. This study adopts the Job demands-Resources Model (Demerouti et al., 2001) and Conservation of Resources Theory (Hobfoll, 1989) as theoretical frameworks. Data were collected through searches in five electronic databases including Scopus, ScienceDirect, Web of Science, Google Scholar, and Portal Garuda using the PRISMA protocol. Of 356 identified articles, 31 articles met the inclusion criteria after quality assessment using the Newcastle-Ottawa Scale and CASP checklist. The review concludes that Job demands tend to negatively affect work engagement , particularly when workload, time pressure, fatigue, and occupational risks are not balanced with adequate job resources. Conversely, work-life balance is positively associated with work engagement , psychological wellbeing, and job satisfaction. Literature synthesis also indicates that excessive Job demands without sufficient work resources increase emotional exhaustion and reduce employee vigor and dedication. However, most studies employed cross-sectional designs, limiting causal interpretation. Furthermore, studies simultaneously examining Job demands, work-life balance, and work engagement within the Indonesian coal mining contractor context remain very limited. These findings highlight the importance of managing work demands and work-life balance to improve employee engagement in mining operational settings.